Changes in Insulin Resistance After Initiation of Raltegravir or Protease Inhibitors With Tenofovir-Emtricitabine: AIDS Clinical Trials Group A5260s. (29th August 2016) - Dirajlal-Fargo, Sahera; Moser, Carlee; Brown, Todd T.; Kelesidis, Theodoros; Dube, Michael P.; Stein, James H.; Currier, Judith; McComsey, Grace A.
Abstract : HIV-infected treatment-naive participants were randomized to tenofovir-emtricitabine (TDF/FTC) plus atazanavir-ritonavir (ATV/r), darunavir-ritonavir (DRV/r), or raltegravir (RAL) over 96 weeks. Insulin resistance increased rapidly and then plateaued and no differences were found with RAL when compared to ATV/r or DRV/r. Abstract: Background. Antiretroviral therapy (ART) can alter glucose metabolism, but little data exist on the association of raltegravir (RAL) with insulin resistance. Methods. A5260s was a substudy of A5257, a prospective open-label randomized trial in which human immunodeficiency virus (HIV)-infected treatment-naive participants were randomized to tenofovir-emtricitabine (TDF/FTC) plus atazanavir-ritonavir (ATV/r), darunavir-ritonavir (DRV/r), or RAL over 96 weeks. Baseline and changes in insulin resistance as estimated by the homeostatic model assessment of insulin resistance (HOMA-IR) were assessed. Wilcoxon rank-sum tests were used to assess shifts in the distribution of fold increase from baseline between treatment arms, and Spearman correlation was used to assess associations between HOMA-IR and measures of inflammation and body composition. Results. Three hundred twenty-eight participants were randomized; 90% were male, baseline median age was 36, HIV ribonucleic acid copies were 4.55 log10 copies/mL, and CD4 cell count was 349/mm 3 . Overall, HOMA-IR increased significantly after 4 weeks (1.9-fold change; 95% confidence interval, 1.73–2.05) then plateaued over the remainder of the study. Changes in HOMA-IR were not different between the arms ( P ≥ .23). Changes in HOMA-IR were associated with changes in body mass index at weeks 48 and 96 ( r = 0.12–0.22; P ≤ .04). There was a trend with increases in HOMA-IR and increases in visceral abdominal fat at week 96 ( r = 0.12; P = .06). At 48 and 96 weeks, HOMA-IR correlated with interleukin-6, high-sensitivity C-reactive protein, and soluble CD163 ( r = 0.16–0.27; P ≤ .003). Conclusions. Insulin resistance increased rapidly and then plateaued in treatment-naive participants initiating ART with TDF/FTC, and no differences were found with RAL when compared with ATV/r or DRV/r.